PENGARUH PENERAPAN METODE EKSPOSITORI TERHADAP HASIL BELAJAR ILMU PENGETAHUAN SOSIAL MURID KELAS V SD MUHAMMADIYAH PERUMNAS KOTA MAKASSAR - Wahyu Pratama; Suardi; Yumriani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the expository method on students'learning outcomes in Social Studies (IPS) subjects for fifth-grade students at SDMuhammadiyah Perumnas, Makassar City. This research employed a quantitativeapproach using a pre-experimental design with a one-group pretest-posttestdesign. The study involved 17 students, consisting of 7 boys and 10 girls. Datawere collected through pretest and posttest assessments and analyzed usingdescriptive and inferential statistics through a paired sample t-test. The analysisresults showed an increase in the average student score from 66.47 (pretest) to82.65 (posttest), with a difference of 16.18 points. The normality test indicated thatthe data were normally distributed (significance = 0.200), and the t-test resultsshowed a significant difference between the pretest and posttest scores(significance = 0.000< 0.05). Therefore, it can be concluded that the expositorymethod has a significant effect on improving studentsSocial Studies learningoutcomes. This method is effective for classroom instruction because it deliversmaterial systematically and enhances students understanding of key concepts inthe subject.